geolocator birds - Morganti, Michelangelo; Rubolini, D.; Akesson, Susanne; Bermejo, Ana; De La Puente, Javier; Lardelli, Roberto; Liechti, Felix; Boano, Giovanni; Tomassetto, Erika; Ferri, Mauro; Caffi, Mario; Saino, Nicola; et al. (Dryad Digital Repository, 2017)
Table having 372 records exclusively belonging to geolocators birds from all the 14 study sites. Geolocator type, weight and appearence (flat vs with light stalk) are indicated. Dataset used to run the model shown in Table 5 of the main text.